Epidemiological, Clinical, and Prognostic Features of Infective Endocarditis: A Retrospective Study with 90 Episodes - Kaçmaz, Asiye Bahar; Balkan, İlker İnanç and Sinan, Ümit Yaşar and Mete, Bilgül and Saltoğlu, Nese and Tabak, Fehmi and Mert, Ali and Küçükoğlu, Mehmet Serdar and Öztürk, Recep (Cerrahpaşa Medical Journal, 2021)
Objective: To evaluate the epidemiological, clinical, microbiological, and echocardiographic features, as well as the prognosis and longterm outcome of patients with infective endocarditis. Methods: The clinical records and follow-up data of 90 endocarditis episodes in 86 patients diagnosed with definite and possible infective endocarditis according to the modified Duke criteria in a tertiary university hospital, between 1998 and 2016, were reviewed. Results: Fifty-six patients were male (65.1%), and the mean age was 49.9 ± 14.3. Native valve endocarditis constituted 62.2% of the cases, while the remaining patients had prosthetic valve endocarditis. The aortic (34.4%) and mitral (24.4%) valves were infected more frequently. Streptococci (27.7%) and staphylococci (24.4%) were the most frequently isolated microorganisms. Embolic complications (35.5%) were the leading cause of morbidity, followed by valve insufficiency (28.8%) and heart failure (21.1%). Valve replacement surgery was performed in 28 patients (31%). The in-hospital mortality rate was 15.1% (n = 13). Chronic renal failure (P = .042) and degenerative valves (P = .036) were significantly associated with mortality. Among 43 of the 73 cases available for telephonic survey, 36 (83.7%) patients were alive and without disease, with a median follow-up of 52.9 (4-163) months. Twenty-five (69.4%) of these patients were younger than 55 years, and 24 (66.6%) had native valve endocarditis. Conclusion: Underlying cardiac conditions and chronic renal failure increase mortality in infective endocarditis, regardless of the pathogen. Long-term survival seems promising in cases with native valve endocarditis and in younger patients with low rates of comorbidities. Cite this article as: Kaçmaz AB, Balkan İİ, Sinan ÜY, et al. Epidemiological, Clinical, and Prognostic Features of Infective Endocarditis: A Retrospective Study with 90 Episodes. Cerrahpaşa Med J. 2021;45(2):107-115.